Lethal severe fever with thrombocytopenia syndrome virus infection causes systemic germinal centre failure and massive T cell apoptosis in cats - Sakai, Yusuke; Mura, Serina; Kuwabara, Yuko; Kagimoto, Saya; Sakurai, Masashi; Morimoto, Masahiro; Park, Eun-sil; Shimojima, Masayuki; Nagata, Noriyo; Ami, Yasushi; Yoshikawa, Tomoki; Iwata-Yoshikawa, Naoko; et al. (Frontiers in Microbiology, 2024)
Introduction: Severe fever with thrombocytopenia syndrome (SFTS) is a fatal viral disease characterized by high fever, thrombocytopenia, leukopenia, and multi-organ haemorrhage. Disruption of the humoral immune response and decreased lymphocyte numbers are thought to contribute to the disease severity. These findings have been obtained through the analysis of peripheral blood leukocytes in human patients, whereas analysis of lymph nodes has been limited. Thus, in this study, we characterized the germinal centre response and apoptosis in the lymph nodes of cats with fatal SFTS, because SFTS in cats well mimics the pathology of human SFTS. Methods: Lymph node tissue sections collected during necropsy from seven fatal SFTS patients and five non-SFTS cases were used for histopathological analysis. Additionally, lymph node tissue sections collected from cats with experimental infection of SFTS virus (SFTSV) were also analysed. Results: In the lymphoid follicles of cats with SFTS, a drastic decrease in Bcl6-and Ki67-positive germinal centre B cells was observed. Together, the number of T cells in the follicles was also decreased in SFTS cases. In the paracortex, a marked increase in cleaved-caspase3 positivity was observed in T cells. These changes were independent of the number of local SFTS virus-positive cell. Furthermore, the analysis of cats with experimental SFTSV infection revealed that the intrafollicular Bcl6-and CD3-positive cell numbers in cats with low anti-SFTSV antibody production were significantly lower than those in cats with high anti-SFTSV antibody production. Discussion: These results suggest that dysfunction of the humoral response in severe SFTS was caused by the loss of germinal centre formation and massive apoptosis of T cells in the lymph nodes due to systemically circulating viruses.